2007
DOI: 10.1021/ja067477g
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MicroRNAs Using Target-Guided Formation of Conducting Polymer Nanowires in Nanogaps

Abstract: A nanogapped microelectrode-based biosensor array is fabricated for ultrasensitive electrical detection of microRNAs (miRNAs). After peptide nucleic acid (PNA) capture probes were immobilized in nanogaps of a pair of interdigitated microelectrodes and hybridization was performed with their complementary target miRNA, the deposition of conducting polymer nanowires, polyaniline (PAn) nanowires, is carried out by an enzymatically catalyzed method, where the electrostatic interaction between anionic phosphate grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(154 citation statements)
references
References 52 publications
3
151
0
Order By: Relevance
“…A similar detection method was developed using polymer-based nanowires. In this study, concentration of miRNA could be quantified in the range of 10 fM-20 pM with a detection limit of 5.0 fM [28].…”
Section: Applicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…A similar detection method was developed using polymer-based nanowires. In this study, concentration of miRNA could be quantified in the range of 10 fM-20 pM with a detection limit of 5.0 fM [28].…”
Section: Applicationsmentioning
confidence: 97%
“…Poly(dimethyl siloxane) (PDMS) is the most commonly used polymer for fabrication of fluidic channels [3,4,11,60] towards biosensor applications though poly(methyl methacrylate) (PMMA) is also used [115]. Conducting polymers such as poly(phenylene vinylene) [23], and its soluble derivatives along with polyaniline have been used for electronic components [28]. The main challenges in working with polymers relate to the relatively lower Young's modulus for these materials making polymer channels more prone to collapse and deformation than either silicon or glass.…”
Section: (A) Materials and Substrates For Biosensor Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a low cost alternative of PNA, antisense morpholino oligos (MCPs), which have higher affinity to complementary RNA than natural nucleic acid probes, were also reported [34]. Despite of the well-documented advantages of using synthetic nucleic acid analogues as selective miRNA probes [21] their implementation in electrochemical detection methodologies is still scarce [35,36]. It must be mentioned that miRNA detection, beside the availability of high affinity and selectivity hybridization probes, benefits also from the implementation of new signaling probes with superior properties.…”
Section: Selective Probes For Mirna Detectionmentioning
confidence: 99%
“…Thus, if microelectrodes are flanking a receptor modified surface, the specific binding of a target can be monitored through conductivity changes it causes in the gap. Fan et al [35] reported a biosensor array consisting of 100 pairs of interdigitated microelectrodes with a gap of 300 nm between adjacent electrodes that features immobilized PNA probes. The selective binding of the target miRNA generated negative charges on the surface, which facilitated in subsequent steps the peroxidase catalyzed deposition of conducting polyaniline nanowires.…”
Section: Mirna Detection By Nanogap Sensorsmentioning
confidence: 99%